Interdisciplinary archaeological prospection, excavation and 3D documentation exemplified through the investigation of a burial at the Iron Age settlement site of Uppåkra in Sweden. Issue 3 (15th March 2015) - Larsson, Lars; Trinks, Immo; Söderberg, Bengt; Gabler, Manuel; Dell'unto, Nicolo; Neubauer, Wolfgang; Ahlström, Torbjörn
ABSTRACT This paper presents the archaeological prospection, excavation and digital three‐dimensional documentation of a previously unknown neolithic grave, presumably late neolithic, at the outstanding Iron Age site of Uppåkra in southern Sweden, and exemplifies a multidisciplinary approach to modern archaeological fieldwork. In the framework of a large‐scale archaeological prospection pilot study conducted at the archaeological site of Uppåkra using remote sensing and large‐scale near‐surface geophysical prospection methods a peculiar circular structure was discovered and mapped using both manual and motorized high‐resolution ground‐penetrating radar (GPR) measurements. The structure, consisting of a ring ditch of ca. 10 m diameter, encloses an east–west oriented strongly reflecting rectangular body in the centre, which therefore was interpreted as being caused by the buried remains of a prehistoric barrow. Subsequent archaeological excavation was conducted across this structure in order to determine the exact cause of the GPR anomaly. This excavation resulted in detailed confirmation of the archaeological prospection results as well as in the discovery of dateable finds. The excavation was documented using the latest image‐based three‐dimensional modelling techniques. Copyright © 2015 John Wiley & Sons, Ltd.